Sri Lanka - Stads, Gert-Jan; Weerahewa, Jeevika; Wijetunga, Chatura Sewwandi; Pham, Nguyen Thi (International Food Policy Research Institute, 2019)
In 2016, Sri Lanka invested 0.62 percent of its AgGDP in agricultural research, representing an increase since 2010. Nevertheless, levels remained below those needed to address the country’s numerous productivity-related challenges. Long-term recruitment restrictions have prevented government agricultural research agencies from expanding their pools of researchers over time. Sri Lanka stands out from most low- and middle-income countries globally in that the majority of its agricultural researchers are female. Comparatively few women hold managerial positions, however.